COMMODIFICATION OF VALUES IN AMERICAN POPULAR FAMILY MOVIES IN 1990S - Siti Harsia; Ida Rochani Adi (Universitas Gadjah Mada, 2020)
This thesis investigates the American popular family films from the 1950s to the 2000s by using Interdisciplinary approach. This approach is intended to explore the object of research from the history, sociology, and cultural background. The theory of representation and commodification are used together to examine how the films represent American family life and how the film industry commercializes American family values. By focusing on family roles that include the division of roles between husband and wife, interactions between family members, and the values adopted by children as a result of parenting practice, it was found that the family concept shown in films from the 1950s to the 2000s represented the reality of the dynamics of family life in every decade. Besides, in popular films of the 1990s, 'Hollywood Family Entertainment' commercialized the patriarchal issues contained in the 'traditional family' concept. There is an ideology of 'ideal woman' strictly as a housewife which was commodified through these films. Optimistic value in the family was also commodified through the child character consistently, shown by the emergence of child character who tends to be positive towards the future, focus on goals, strives for success and happiness and free in making choices.